Case report of a Li–Fraumeni syndrome-like phenotype with a de novo mutation in CHEK2. Issue 29 (July 2016) - Zhuang, Xuehan; Li, Yongping; Cao, Hongzhi; Wang, Ting; Chen, Jianghao; Liu, Jiayun; Lin, Liya; Ye, Rui; Li, Xinyang; Liu, Shuang; Li, Weiyang; Lv, Yonggang; et al.
Abstract: Background: Cases of multiple tumors are rarely reported in China. In our study, a 57-year-old female patient had concurrent squamous cell carcinoma, mucoepidermoid carcinoma, brain cancer, bone cancer, and thyroid cancer, which has rarely been reported to date. Methods: To determine the relationship among these multiple cancers, available DNA samples from the thyroid, lung, and skin tumors and from normal thyroid tissue were sequenced using whole exome sequencing. Results: The notable discrepancies of somatic mutations among the 3 tumor tissues indicated that they arose independently, rather than metastasizing from 1 tumor. A novel deleterious germline mutation (chr22:29091846, G->A, p.H371Y) was identified in CHEK2, a Li–Fraumeni syndrome causal gene. Examining the status of this novel mutation in the patient's healthy siblings revealed its de novo origin. Conclusion: Our study reports the first case of Li–Fraumeni syndrome-like in Chinese patients and demonstrates the important contribution of de novo mutations in this type of rare disease. Abstract : Supplemental Digital Content is available in the text